PERSPEKTIF HUKUM ADMINISTRASI TERHADAP TILANG SURAT TANDA NOMOR KENDARAAN BERMOTOR YANG BELUM MEMBAYAR PAJAK - Yosephine Tita, Heillen Martha; Mustamu, Julista (Gapenas Publisher, 2025)
Motor Vehicle Registration Certificate is one of the mandatory equipment for driving on the highway. In the tax administration process, this document is also used as proof of payment of Motor Vehicle Tax. The use of the same document in two different legal events, in principle, is an effort to make the use of the document more effective, but it is controversial in law enforcement of Police Operations on the highway, related to the issuance of Traffic Tickets by the Police and a series of sanction settlements. The study from an administrative law perspective aims to answer the invalidity of Motor Vehicle Registration Certificates that have not paid tax as an administrative law event.